2019
DOI: 10.1038/s41586-019-1653-x
|View full text |Cite
|
Sign up to set email alerts
|

Habenular TCF7L2 links nicotine addiction to diabetes

Abstract: Diabetes is far more prevalent in smokers than non-smokers, but little is known about underlying mechanisms of vulnerability. Here, we show that the diabetes-associated gene Tcf7l2 is densely expressed in the medial habenula (mHb), where it regulates the function of nicotinic acetylcholine receptors. Inhibition of Tcf7l2 signaling in the mHb increases nicotine intake in mice and rats. Nicotine elevates blood glucose levels through a Tcf7l2-dependent stimulatory action on the mHb. Virus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 47 publications
0
79
0
1
Order By: Relevance
“…Interestingly, UK biobank studies have recently shown that GPR151 loss-of-function alleles are associated with lower body mass index and protection from diabetes type 2 (44). Related to this, we have recently found that nicotine acts on MHb neurons, which are polysynaptically connected to the pancreas, to stimulate increases in blood glucose levels, and prolonged exposure to this action of nicotine can precipitate the emergence of diabetes in laboratory rodents (39). This suggests that GPR151 may influence diabetes vulnerability, particularly in smokers, by regulating MHb function.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, UK biobank studies have recently shown that GPR151 loss-of-function alleles are associated with lower body mass index and protection from diabetes type 2 (44). Related to this, we have recently found that nicotine acts on MHb neurons, which are polysynaptically connected to the pancreas, to stimulate increases in blood glucose levels, and prolonged exposure to this action of nicotine can precipitate the emergence of diabetes in laboratory rodents (39). This suggests that GPR151 may influence diabetes vulnerability, particularly in smokers, by regulating MHb function.…”
Section: Discussionmentioning
confidence: 77%
“…Phosphorylation by cAMP-dependent kinases regulates the rate of desensitization of nAChRs (38), and specific PKA phosphorylation sites are modulated differently by acute or chronic exposure to nicotine (36,37). It has also been shown that deficits in cAMP signaling can alter nicotine intake in mice (39). Given our demonstration that loss of Gpr151 alters the frequency of spontaneous mEPSCs without altering their amplitude, and that it is present on SVs carrying SV2A and other core proteins, it is probable that GPR151 can act directly on the core complex to regulate vesicle release.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some caveats to consider. TCF7L2 is expressed not only in the mHb, but also in 6 report that activation of these receptors in mice also leads to increases in the release of glucagon and insulin hormones from the pancreas. This leads to increased blood sugar levels -a change associated with an increased risk of diabetes in humans.…”
Section: G I U S E P P E B R U S C H E T Ta and S A B R I N A D I A N Omentioning
confidence: 94%
“…These neurons promote aversive responses to nicotine, but until now, no one knew whether they also control the diabetes-associated effects of smoking -and if so, how. On page 372, Duncan et al 6 identify a signalling pathway that links nAChR-expressing neurons and blood-glucose regulation by the pancreas. It involves a diabetes-associated transcription factor, TCF7L2.…”
Section: G I U S E P P E B R U S C H E T Ta and S A B R I N A D I A N Omentioning
confidence: 99%
See 1 more Smart Citation